2016
DOI: 10.1213/ane.0000000000001633
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Administration Controls MicroRNAs Alterations Observed After Lung Ischemia–Reperfusion Injury

Abstract: Lung IRI caused dysregulation miRNA. The administration of lidocaine reduced significantly miRNAs alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…In response to lidocaine treatment, the cells expressed different miRNAs patterns, possibly via which lidocaine exerted its specific function [24,25]. To date, several miRNAs have been mentioned as the effector genes of lidocaine, such as miR-520-3p [22], miR-493 [26], and miR-let-7b [27].…”
Section: Discussionmentioning
confidence: 99%
“…In response to lidocaine treatment, the cells expressed different miRNAs patterns, possibly via which lidocaine exerted its specific function [24,25]. To date, several miRNAs have been mentioned as the effector genes of lidocaine, such as miR-520-3p [22], miR-493 [26], and miR-let-7b [27].…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference between the control and lidocaine groups in the duration of the ischaemic period (123.3 ± 8.16 min and 127.5 ± 8.89 min, respectively). Haemodynamic parameters were stable during the entire procedure, confirming previous results [24].…”
Section: Resultssupporting
confidence: 89%
“…First, we used juvenile animals which could present an inflammatory response slightly different from that in adults. However, the main concern when using young animals is about the haemodynamic stability which we observed remained stable during the experiments [24]. Other studies investigating the inflammatory response observed after lung surgery used similar animals [39].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Lidocaine may provide protection against IR injury by preventing miRNA dysregulation. A recent study found that lung IR injury caused miRNA dysregulation, while lidocaine reduced these changes [78]. Further studies should be conducted to examine how lidocaine regulates miRNA expression.…”
Section: Regional Anesthesiamentioning
confidence: 99%